THE EFFECT OF KUNDALINI ON MUAC AND BODY WEIGHT IN 1ST TRIMESTER WITH EMESIS GRAVIDARUM - putri, herdian; farokah, Atik; Naqiyyah Khusmitha, Qatrunnada (UNIVERSITAS AIRLANGGA, 2025)
Background: Emesis gravidarum is a discomfort that occurs in mothers during early pregnancy. If emesis gravidarum is not adequately managed, children are more likely to experience stunting. There may be negative impact on health from stunting. Stunting is a health problem that is still the government's current focus. Kundalini yoga is a physical activity that focuses on breathing, so it is hoped that it can divert nausea. When the nausea disappears it will be increase appetite so it can impact to a person's nutritional intake, which can be seen from an increase in MUAC and body weight. The purpose of this study is to evaluate whether kundalini yoga is associated with increased MUAC and body weight in women who have emesis gravidarum. Method: This study used a pre-test and post-test control group design as a quasi-experiment that provided kundalini yoga intervention for 15 minutes every day for 30 days. The study population comprised 20–35 year old pregnant women experiencing mild–moderate nausea and vomiting throughout the 1st trimester of their pregnancy. Using the total sampling technique, samples were collected. In this study, body weight gain (BW) and upper arm circumference (MUAC) were the dependent variables, whereas kundalini yoga was the independent variable. The tools used are body measuring tape and body scales. The independent t-test used to examine variations in body weight and upper arm circumference. Result: In the intervention group, the MUAC addition was 0.096 cm, while in the control group, it was 0.012 cm (p = 0.08). Weight gain was 0.512 kg in the control group and 0.952 kg in the intervention group (p = 0.096). Conclusion: Kundalini yoga was not significant in increasing MUAC and body weight.